Desain Pembelajaran Dalam Kelas Multikultural - Mahlil Harahap (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas Gunung Tua, 2024)
This study examines the design of learning in a multicultural classroom with the primary aim of developing students who are democratic, humane, and pluralistic. Amidst cultural diversity in the classroom, the learning design must be crafted in a way that facilitates effective understanding and mastery of the subject matter, as well as enhances students' competencies. Through a multicultural education approach, it is expected that students will not only master the subjects well but also develop an inclusive attitude that respects differences in their learning environment. The appropriate implementation of learning design is anticipated to create a classroom atmosphere that supports cultural integration and fosters the development of democratic, humane, and pluralistic attitudes among students.